Madame Grès - Blake, Catherine; Paul, Gill ([Veurne] : Hannibal Publishing, 2011)
Accompanies an exhibition at the MoMu Fashion Museum, Province of Antwerp from September - February 2013. A remarkable couturier, with a career spanning half a century, Madame Alix Grès (1903-1993) was known for using delicate pleats which turned ordinary fabric into Grecian-style. This is the first monograph of her extraordinary work. Madame Grès launched her design house under the name Grès in Paris in 1942. Formally trained as a sculptress, she produced haute couture designs for an array of fashionable women, including the Duchess of Windsor, Marlene Dietrich, Greta Garbo, Jacqueline Kennedy, and Dolores del Rio. Her signature was cut-outs on gowns that made exposed skin part of the design, yet still had a classical, sophisticated feel. She was renowned for being the last of the haute couture houses to establish a ready-to-wear line.
Text Dutch-English
boek
Keywords: Grès, Alix